A review of the science and clinical use of alcohol-based hand rubs - Lo, Elaine Ah-Gi; Law, Lawrence Siu-Chun; Tan, Kevin; Ashokka, Balakrishnan (International Journal of Infection Control, 2022)
Alcohol has a longstanding history as an antiseptic, and the coronavirus disease 2019 (COVID-19) pandemic has sparked a renewed interest in its use as a hand sanitizer. Alcohol works by denaturing protein and rendering cell membranes permeable. It offers excellent germicidal effects against Gram-positive and Gram-negative bacteria, Mycobacterium tuberculosis, fungi, and lipid-containing viruses. However, it is less reliable against non-lipid containing viruses and is ineffective against bacterial and fungal spores. Alcohol-based hand rub (ABHR) usually contains 60–90% isopropanol or ethanol. Additives such as chlorhexidine to complement the action of alcohol and emollients to ameliorate the drying effect of alcohol are often included to improve the formulation of ABHR. In the clinical setting, ABHR provides biocidal activity against multidrug resistant bacteria such as methicillin-resistant Staphylococcus aureus as well as viruses like human coronavirus, severe acute respiratory syndrome coronavirus, and Middle East respiratory syndrome. Moreover, its use is associated with an improved compliance with hand hygiene, which has been shown to translate into better patient outcomes. However, there are cases of intoxications secondary to ingestion of ABHR or adulterated alcohol when resources are diverted away from the normal beverage production to meet the increased need for hand sanitizer during the COVID-19 pandemic. The risk of unintentional topical absorption and fire hazard among healthcare workers is low but should not be ignored. We proposed recommendations to mitigate the risk of ABHR ingestion and poisoning as well as that of fire hazard.